Black Widow & Hawkeye. Broken arrow - Phillips, Stephanie, 1991- (Marvel Worldwide, Inc., 2024)
"In the days when the Black Widow and Hawkeye had no one to trust, they still had each other--even though their paths sometimes diverged. So when Clint Barton is accused of a rogue assassination attempt that puts the U.S. and Madripoor at odds, a symbiote-equipped Natasha Romanoff thinks nothing of coming to his aid. But as echoes of their past ripple into the present, it will take all their faith in each other--and the lessons learned along the way--to protect their futures!" --